Synthesis and fabrication of trimetallic (Ru-Mn Co) catalyst supported on TiO2 and Ni(OH)2 thin films for photoelectrochemical applications / Ahmad Nazeer Che Mat - Ahmad Nazeer , Che Mat (2020)
Anatase supported heterogeneous photocatalyst consisting of RuO2, MnO2 and Co3O4 (1:13:13 ratio) was synthesized by precipitation method. The film of the prepared catalyst was fabricated by electrophoretic deposition technique in an aqueous solution of 0.1 mM ammonia and tested for photoelectrocatalytic (PEC) oxidation of methanol in 0.1M KOH under visible light irradiation. The as-prepared photocatalyst was characterized by FTIR, UV–Vis, XRD, Raman spectroscopy, FESEM/EDX, TEM, BET, XPS and TPR. The PEC study by cyclic voltammetry indicates that the oxidation of methanol to CO2 and H2O upon exposure to visible light occurs between 400 and 800 nm. The smaller value of the charge transfer resistance (Rct) of the RuO2-MnO2-Co3O4 supported anatase TiO2 electrode indicates a faster rate of charge transfer at the electrode-electrolyte interface compared to the TiO2 catalyst, which could be promising for direct methanol fuel cell application. Additionally, the trimetallic photocatalysts namely RuO2-MnO2-Co3O4 (1:13:13 ratio) supported anatase TiO2 also was tested for photoelectrochemical reduction of CO2 into formic acid in 0.2 M LiClO4 in aqueous and N,N-dimethylformamide (DMF) under visible light. The photocurrent density in aqueous medium is higher than DMF with the value of 12 μA/cm2 vs Ag/AgCl. The stable photocurrent from chronoamperometry revealing of good discernment of product where formic acid remains the major product in both aqueous and DMF medium. Furthermore, the photoelectrochemical reduction of CO2 in aqueous and N,N-dimethylformamide (DMF) was also investigated over spherical Ni(OH)2 photocatahode in 0.2 M LiClO4 prepared by hydrothermal method was investigated under visible light irradiation. The band gap of Ni(OH)2 obtained from UV-Vis spectroscopy was 1.8 eV which enabled efficient visible light absorption for the photoreaction. The porous spherical morphology of Ni(OH)2 allows deeper penetration of light onto the active sites for better photocatalytic performance. The photocurrent density in aqueous and DMF solution at 0.2 V (vs. Ag/AgCl) were 24 mA/cm2 and 5 mA/cm2, respectively. Acetaldehyde and methanol are the major products in aqueous solution, while formic acid and methanol were the major products in DMF, after 6 hours of photoelectrolysis. The products formation from the photoelectrochemical reduction of dissolved CO2 were 612 and 854 ppm in aqueous and DMF, respectively.